Sosialisasi Pemilahan Sampah kepada Siswa Kelas 1 SDIT Ikhtiar - Makassar - Asiyanthi Tabran Lando; Abdul Nasser Arifin .; Irwan Ridwan Rahim .; Kartika Sari .; Ibrahim Djamaluddin .; Annisa Dwi Damayanti .; Anugrah Jihadi . (Faculty of Engineering UNHAS, 2022)
Children's awareness in disposing of waste in its place is one of the important factors in learning environmental health to be healthy and clean. The basics and concepts of waste management are not merely using advanced technology, but rather require changes and the formation of behavior from each individual. The formation of individual behavior in managing waste properly needs to be instilled from an early age, which is the golden age of forming a person's behavior, which will become easier and the results more visible at a later age. The formation of waste management behavior from an early age can be started from the formation of the habit of sorting and placing waste in its place, which is expected to become a habit in the course of his life. So that togetherness in managing and creating a clean and healthy environment will be more easily realized. Partners involved in this Community Service activity are students and teachers at SDIT Ikhtiar-Makassar. The solution offered is socialization and assistance to students to dispose of waste in the provided trash cans, separate organic waste, inorganic waste, and B3 waste, and minimize waste generation with the 3R concept (Reuse, Reduce, Recycle). During the COVID-19 pandemic, direct socialization activities were replaced by handing over a pocketbook on waste sorting which contains instructions on how to sort waste. This pocketbook will be used as material in thematic learning for SDIT Ikhtiar students and as one of the supports for the school's Adiwiyata program.